Reversed Halo Sign as an Unusual Manifestation of Cryptogenic Organized Pneumonia. Report of One Case [Signo del Halo Invertido Como Manifestación Inhabitual de Neumonía Organizada Criptogénica. Reporte de Un Caso] - Martinez-Diaz, P (Sociedad Medica de Santiago, 2019)
We report a 64 years old female admitted with fever, cough, dyspnea and lung opacities in the chest X ray. A chest tomography scan (CTS) showed multi-ple-bilateral ring-shaped opacities and the reversed halo sign (RHS). The patient did not improve with antimicrobial therapy (AT). Infection and rheumatologic causes were excluded, therefore Cryptogenic organizing pneumonia (COP) was suspected with compatible percutaneous biopsy. Systemic steroids were started with a good clinical response. The patient was discharged four weeks after admission in good general conditions and practically no lungs opacities. © 2019, Sociedad Medica de Santiago. All rights reserved.